3(8x-3)=7(4x+1)

Simple and best practice solution for 3(8x-3)=7(4x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(8x-3)=7(4x+1) equation:



3(8x-3)=7(4x+1)
We move all terms to the left:
3(8x-3)-(7(4x+1))=0
We multiply parentheses
24x-(7(4x+1))-9=0
We calculate terms in parentheses: -(7(4x+1)), so:
7(4x+1)
We multiply parentheses
28x+7
Back to the equation:
-(28x+7)
We get rid of parentheses
24x-28x-7-9=0
We add all the numbers together, and all the variables
-4x-16=0
We move all terms containing x to the left, all other terms to the right
-4x=16
x=16/-4
x=-4

See similar equations:

| 8x+-4=26-3 | | x+2+2x+13+10=90 | | x+2+2x+13+10=180 | | 4√x=44.4 | | 2.25÷1.5=n | | 200=5x+5x | | 12/x=0.26 | | (x)/(11)-9=-7 | | X+11=7y | | 6x+36=32 | | 4x−7=5x | | 4⋅x−7=5⋅x | | 8-4x=6x+9 | | 7x=-2x-54 | | 2(1+2x)=2(-2x+14)/2 | | (6+y)/y-y/2=3 | | 22x=19x+42 | | 6+y/y-y/2=3 | | (2x+3)/4=(5x-2)/3 | | |(3)/(4)x-1|=7 | | x2+5x-9,75=0 | | (x+11)(x–11)=104 | | |2x|-4=3 | | x2+45=126 | | 2|x|-4=3 | | 44–y=25–2(8–3y) | | 4x-40=6x+12 | | (315+2x)-(103+x)=224 | | 3(2y-5)=21 | | 13x2+17x=0 | | 2c+1=21 | | 10x–5=34–3x |

Equations solver categories